2011
DOI: 10.3727/096368910x532783
|View full text |Cite
|
Sign up to set email alerts
|

Using Self-Assembled Nanomaterials to Inhibit the Formation of Metastatic Cancer Stem Cell Colonies in Vitro

Abstract: The isolation of cells with stem-like properties from prostate tumors suggests the presence of a cancer stem cell (CSC) population, which may account for the initiation, progression, and metastasis as well as drug resistance of the disease. We hypothesized that containing, or at least immobilizing, the CSCs in a nanoself-assembling material might help prevent prostate tumor progression or metastasis. CSCs were plated in three conditions: 1) placed in 1% concentration self-assembled peptide (SAP) preequilibrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…In a recent study, Ellis-Behnke and coworkers have reported that self-assembling peptide could inhibit the formation of metastatic prostate cancer stem cell colonies in vitro [49]. The result showed that the prostate cancer stem cells DU145 placed in the RADA16-I peptide hydrogel stopped both the division of cancer cells in vitro and subsequent colony formation for up to 28 days.…”
Section: In Another Study Zhao and Colleagues Have Investigated The mentioning
confidence: 95%
“…In a recent study, Ellis-Behnke and coworkers have reported that self-assembling peptide could inhibit the formation of metastatic prostate cancer stem cell colonies in vitro [49]. The result showed that the prostate cancer stem cells DU145 placed in the RADA16-I peptide hydrogel stopped both the division of cancer cells in vitro and subsequent colony formation for up to 28 days.…”
Section: In Another Study Zhao and Colleagues Have Investigated The mentioning
confidence: 95%
“…33 Research by Ling et al has suggested that self-assembling peptide can inhibit the formation of metastatic prostate CSC colonies in vitro, while preserving its viability and CSC property. 34 Our results show that the CD44 + /CD24 -cell populationenriched breast cancer cell line adopts various morphologies in different 3D culture scaffolds in response to cues from the extracellular matrix. In this assay, the disorganized malignant phenotype of the cells can partially be reverted to a phenotype much more closely approximating that of nonmalignant breast acini in RADA16 3D cultures.…”
Section: Discussionmentioning
confidence: 88%
“…Because peptides are synthesized from amino acids, the degradation of the peptidebased scaffolds would lead to no immune response and side effects (Kopecek and Yang 2009;Zhao et al 2010). Moreover, these reported self-assembly peptide nanofiber scaffolds are with high water content, mimicking the natural extracellular matrix, and have been shown to be useful in 3D cell culture, tissue repair, and regeneration (Collier et al 2010;EllisBehnke et al 2006a, b;Guo et al 2007;Kopecek and Yang 2009;Ling et al 2011;Zhao et al 2010). One interesting application is to engineer the peptide molecules with side chains of pharmaceutical effects (Zhao et al 2010), and the hydrogel during biological degradation will guide the drug release reactions.…”
Section: Nano-gelmentioning
confidence: 99%